Global burden, trends, and inequalities of gastric cancer attributable to high-sodium diets: a 30-year analysis and projections based on the global burden of disease 2021 study - Tian, Qiangqiang; Zheng, Ya; Li, Yishudong; Wu, Rui; Lin, Yuyu; Chen, Zhaofeng (Frontiers in Nutrition, 2025)
BackgroundHigh-sodium diet is a modifiable risk factor for gastric cancer, contributing substantially to its global burden. However, comprehensive evaluations of temporal, geographic, and sociodemographic patterns remain limited.MethodsUsing Global Burden of Disease (GBD) 2021 data, we systematically assessed gastric cancer mortality and disability-adjusted life years (DALYs) attributable to high-sodium diets across 204 countries and territories from 1990 to 2021. Analytical approaches included joinpoint regression, age-period-cohort models, frontier efficiency, inequality metrics, and Bayesian projections to 2036.ResultsGlobally, age-standardized mortality and DALY rates declined significantly from 1990 to 2021 (EAPC for mortality: −2.26%; DALYs: −2.88%). The highest burden was observed in East Asia, with China and Mongolia being most affected. Disparities across sex, region, and sociodemographic index (SDI) persisted, with middle and high-middle SDI countries exhibiting peak age-standardized rates. Reductions were most pronounced in high SDI and high-income Asia-Pacific regions. Inequality, while reduced in absolute terms, remained evident. Projections indicate continued declines, but persistent regional differences.ConclusionsDespite global progress in reducing age-standardized rates, substantial absolute and relative disparities in gastric cancer burden attributable to high-sodium diets persist, especially in transitioning economies. Targeted policies combining sodium reduction, education, regulation, and improved healthcare access are vital to accelerate progress and achieve more equitable health gains worldwide.